Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1996
DOI: 10.1148/radiology.200.3.8756914
|View full text |Cite
|
Sign up to set email alerts
|

Solitary pulmonary nodules: MR evaluation of enhancement patterns with contrast-enhanced dynamic snapshot gradient-echo imaging.

Abstract: Dynamic contrast-enhanced MR measurements of tumor enhancement can provide additional information about the nature of SPNs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 88 publications
(74 citation statements)
references
References 0 publications
5
68
0
1
Order By: Relevance
“…Our study techniques involved a quantitative method based on a whole nodule perfusion measurement and rapid dynamic acquisitions focused on the first pass of contrast material, as this early phase seemed to be very important to the differentiation of malignant from benign SPNs [2,4,10]. By using a 64-dectector row CT scanner, a 40 mm volume tissue coverage along the z-axis was available, which encompassing the entire nodule.…”
Section: Discussionmentioning
confidence: 99%
“…Our study techniques involved a quantitative method based on a whole nodule perfusion measurement and rapid dynamic acquisitions focused on the first pass of contrast material, as this early phase seemed to be very important to the differentiation of malignant from benign SPNs [2,4,10]. By using a 64-dectector row CT scanner, a 40 mm volume tissue coverage along the z-axis was available, which encompassing the entire nodule.…”
Section: Discussionmentioning
confidence: 99%
“…2 and 3). It has therefore been suggested that enhancement patterns or blood supply evaluated with dynamic contrast-enhanced MR imaging may be helpful for diagnosis and management of pulmonary nodules (Kono et al 1993(Kono et al , 2007Kusumoto et al 1994;Hittmair et al 1995;Gückel et al 1996;Fujimoto et al 2003;Ohno et al 2002Ohno et al , 2004aSchaefer et al 2004Schaefer et al , 2006Donmez et al 2007). However, it may be possible to diagnose several histological types of pulmonary nodules, such as bronchocele, tuberculoma, mucinous bronchoalveolar carcinoma (BAC), hamartoma, and aspergilloma, on pre-or post-contrastenhanced T1-weighted images and T2-weighted image according to their specific MR findings.…”
Section: Characterization and Management Of Pulmonary Nodules Or Massmentioning
confidence: 99%
“…These curves represent first transit and/or recirculation and washout of contrast media in irregularly thickened cavity wall as, respectively, low and high signal intensities in the left lower lobe. Post-contrast black-blood T1-weighted turbo SE (e) image shows wellenhanced cavity wall corresponding to lung cancer 5 min or more with repeated breath holding (Kono et al 1993(Kono et al , 2007Kusumoto et al 1994;Hittmair et al 1995;Gückel et al 1996;Ohno et al 2002Ohno et al , 2004aFujimoto et al 2003;Schaefer et al 2004Schaefer et al , 2006Donmez et al 2007). Taking into account the inherent inhomogeneous composition of many intraindividual lung cancers and even within benign lesions such as central necrosis, only a dynamic show intracavitary lesion as, respectively, low and very low signal intensities in the left upper lobe.…”
Section: Dynamic Contrast-enhanced Mr Imaging Of Pulmonary Nodulesmentioning
confidence: 99%
See 2 more Smart Citations